School Laboratory Management - Chevi Ardiana; Lida Amalia; Rifaatul Muthmainnah; Irpan Nawawi; Dewi Hernawati (Indonesian Journal of Community Empowerment (IJCE), 2022)
Abstract The laboratory is a facility or place where there are scientific activities (practicum/research) to produce a scientific product (result). The existence of a lab rotaroium in schools is very necessary as a support for learning in the classroom. The main function of the laboratory is to study and prove a certain theory and to find or produce a scientific product (result). The laboratory becomes a means of practice for certain subjects that require practical activities. Based on these facts, it is necessary to manage the school laboratory. School laboratory management is needed so that the laboratory can run according to its function. The method used is an online lecture which contains an explanation of the basic concepts of laboratory management materials. The data analysis technique used is descriptive. The result of Pengabdian kepada Masayarakat is participants' understanding of how to properly manage school laboratories and their application so that laboratory management can run regularly in the school environment (SMP/MTS, SMA/MA). Abstrak Laboratorium merupakan sarana atau tempat dimana terdapat kegiatan ilmiah (praktikum/penelitian) untuk menghasilkan suatu produk (hasil) ilmiah. Keberadaan labarotaroium di sekolah sangat diperlukan sebagai penunjang pembelajaran di kelas. Fungsi utama Laboratorium adalah mempelajari dan pembuktian suatu teori tertentu serta menemukan atau menghasilkan suatu produk (hasil) ilmiah. Laboratorium menjadi sarana praktek bagi mata pelajaran tertentu yang membutuhkan kegiatan praktikum. Berdasarkan fakta tersebut maka diperlukan pengelolaan laboratorium sekolah. Pengelolaan laboratorium sekolah diperlukan agar laboratorium dapat berjalan sesuai dengan fungsinya. Metode yang digunakan berupa ceramah secara daring berisi penjelasan konsep – konsep dasar materi pengelolaan laboratorium dan teknik analisis data yang digunakan adalah deskriptif. Hasil dari pengabdian masyarakat ini adalah pemahaman peserta tentang bagaiamana mengelola laboratorium sekolah dengan benar beserta penerapannya sehingga pengelolaan laboratorium dapat berjalan secara berkala di lingkungan sekolah (SMP, SMA/MA).